IMPLEMENTASI PEDOMAN PELAKSANAAN MUSYAWARAH PERENCANAAN PEMBANGUNAN - Joko Susanto; Andriyanto Andriyanto (Pelantar Press, 2023)
Women's participation in development planning and budgeting in the Development Planning Consultation (Musrenbang) is still a challenge to date. In response to this, the Trenggalek Regency Government has issued a policy in the form of Regent Regulation Number 01 of 2019 which guides the implementation of deliberations on women, children, disabilities and other vulnerable families. Or abbreviated as Musrena Keren. This public policy publication provides opportunities for the full participation of women and vulnerable families in gender mainstreaming (PUG) and gender-responsive budgeting (ARG) from the lowest level, namely at the village level. This research aims to comprehensively detail the innovation of Musrena Keren in Trenggalek District. Using a qualitative approach, data for this study was collected from focus group discussions (FGDs), in-depth interviews and desk review (documentary review). The results of this research are: 1. Increased motivation and awareness of women at the village and district levels in participating in gender-responsive budgeting and development planning. 2. Musrena Keren is based on the principles of equality, gender-equitable budgeting, dialogue, fighting domination, siding with vulnerable groups, non-discrimination and inclusive development.